2011
DOI: 10.1111/j.1750-3841.2010.02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Action of Binary and Ternary Mixtures of Carvacrol, Thymol, and Eugenol against Listeria innocua

Abstract: The bactericidal effect of 3 natural agents (carvacrol, thymol, and eugenol) was evaluated as well as their binary and ternary mixtures on Listeria innocua inactivation in liquid model systems. Minimal bactericidal concentrations (MBC) of these agents were determined, and then binary and ternary mixtures were evaluated. Culture media were inoculated with L. innocua and incubated for 72 h at 35 °C. Turbidity of studied systems were determined every 24 h. The most effective individual antimicrobial agent was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(75 citation statements)
references
References 31 publications
2
70
0
3
Order By: Relevance
“…Numerous studies have demonstrated the bactericidal [30], fungicidal [31] and insecticidal [32] activity of CAR. CAR has shown anti-tumorigenic activity in hepatocellular carcinoma, both in vitro and in vi o [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the bactericidal [30], fungicidal [31] and insecticidal [32] activity of CAR. CAR has shown anti-tumorigenic activity in hepatocellular carcinoma, both in vitro and in vi o [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that p-cymene induces swelling of bacterial cell membranes that enable easier entry of carvacrol into the cell membrane [49]. García-García et al [50] found the most Allium sativum (Garlic) belongs to family Liliaceae is a perennial bulb-forming plant. Garlic has been used for dietary and therapeutic purposes [51].…”
Section: Synergy Among Herbal Antimicrobialsmentioning
confidence: 99%
“…They can be sourced from over 1,300 plants such as thyme (thymol), oregano (carvacrol), clove (eugenol), orange (limonene), and cinnamon (cinnamaldehyde) (Chao et al 2000;Velluti et al 2003;Holley and Patel 2005). Phenolic compounds such as thymol, carvacrol and eugenol are known as EOs possessing the most potent antibacterial properties (García-García et al 2011). Recent demonstration states that, the inhibition of a wide range of bacterial species, including, E. coli O157:H7, Listeria monocytogenes, Staphylococcus aureus, Salmonella typhymurium (Oussalah et al 2007) and several other fungi by essential oil treatment (De Martino et al 2009).…”
Section: Introductionmentioning
confidence: 99%